Imperfect Information and Staggered Price Setting - Ball, Laurence; Cecchetti, Stephen G. (American Economic Review, 1988)
Many Keynesian macroeconomic models are based on the assumption that firms change prices at different times. This paper presents an explanation for this "staggered" price setting. We develop a model in which firms have imperfect knowledge of the current state of the economy and gain information by observing the prices set by others. This gives each firm an incentive to set its price shortly after other firms set theirs. Staggering can be the equilibrium outcome. In addition, the information gains can make staggering socially optimal even though it increases aggregate fluctuations.